Hydrogenation of titanocene and zirconocene bis(trimethylsilyl)acetylene complexes - Pinkas, Jiří; Gyepes, Róbert; Císařová, Ivana; Kubišta, Jiří; Horáček, Michal; Žilková, NaděŽda; Mach, Karel (Dalton transactions (Cambridge, England, 2018)
Reactions following the addition of dihydrogen under maximum atmospheric pressure to bis(trimethylsilyl)acetylene (BTMSA) complexes of titanocenes, [(η5-C5H5-nMen)2Ti(η2-BTMSA)] (n = 0, 1, 3, and 4) (1A-1D), and zirconocenes, [(η5-C5H5-nMen)2Zr(η2-BTMSA)] (n = 2-5) (4A-4D), proceeded in diverse ways and, depending on the metal, afforded different products. The former complexes lost, in all cases, their BTMSA ligand via its hydrogenation to bis-1,2-(trimethylsilyl)ethane when reacted at 80 °C for a prolonged reaction time. For n = 0, 1, and 3, the titanocene species formed in situ dimerised via the formation of fulvalene ligands and two bridging hydride ligands, giving known green dimeric titanocenes (2A-2C). For n = 4, a titanocene hydride [(η5-C5HMe4)2TiH] (2D) was formed, similarly to the known [(η5-C5Me5)2TiH] (2E) for n = 5; however, in contrast to this example, 2D in the absence of dihydrogen spontaneously dehydrogenated to the known Ti(iii)-Ti(iii) dehydro-dimer [{Ti(η5-C5HMe4)(μ-η1:η5-C5Me4)}2] (3B). This complex has now been fully characterised via spectroscopic methods, and was shown through EPR spectroscopy to attain an intramolecular electronic triplet state. The zirconocene-BTMSA complexes 4A-4D reacted uniformly with one hydrogen molecule to give Zr(iv) zirconocene hydride alkenyls, [(η5-C5H5-nMen)2ZrH{C(SiMe3)[double bond, length as m-dash]CH(SiMe3)}] (n = 2-5) (5A-5D). These were identified through their 1H and 13C NMR spectra, which show features typical of an agostically bonded proton, [double bond, length as m-dash]CH(SiMe3). Compounds 5A-5D formed equilibria with the BTMSA complexes 4A-4D depending on hydrogen pressure and temperature.